Nanozyme-based sensing of dopamine using cobalt-doped hydroxyapatite nanocomposite from waste bones - Nishan, Umar; Jabeen, Nighat; Badshah, Amir; Muhammad, Nawshad; Shah, Mohibullah; Ullah, Irfan; Afridi, Saifullah; Iqbal, Jibran; Asad, Muhammad; Ullah, Riaz; Ali, Essam A.; Ahmed, Sarfraz; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Dopamine is one of the most important neurotransmitters and plays a crucial role in various neurological, renal, and cardiovascular systems. However, the abnormal levels of dopamine mainly point to Parkinson's, Alzheimer's, cardiovascular diseases, etc. Hydroxyapatite (HAp), owing to its catalytic nature, nanoporous structure, easy synthesis, and biocompatibility, is a promising matrix material. These characteristics make HAp a material of choice for doping metals such as cobalt. The synthesized cobalt-doped hydroxyapatite (Co-HAp) was used as a colorimetric sensing platform for dopamine. The successful synthesis of the platform was confirmed by characterization with FTIR, SEM, EDX, XRD, TGA, etc. The platform demonstrated intrinsic peroxidase-like activity in the presence of H 2 O 2 , resulting in the oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB). The proposed sensor detected dopamine in a linear range of 0.9-35 µM, a limit of detection of 0.51 µM, limit of quantification of 1.7 µM, and an R 2 of 0.993. The optimization of the proposed sensor was done with different parameters, such as the amount of mimic enzyme, H 2 O 2 , pH, TMB concentration, and time. The proposed sensor showed the best response at 5 mg of the mimic enzyme, pH 5, 12 mM TMB, and 8 mM H 2 O 2 , with a short response time of only 2 minutes. The fabricated platform was successfully applied to detect dopamine in physiological solutions.